Human Resource Development In Improving the Performance of Lecturers Majoring in Management, Pattimura University, Ambon - Leuhery, Ferdy (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
The performance of lecturers plays a crucial role in achieving educational goals, and the lack of adequate human resource development can hinder the quality of teaching. This research was conducted to develop human resources and improve the performance of Management Department lecturers at Pattimura University Ambon. Using qualitative research methods, in-depth interviews with lecturers and staff in the department were conducted, along with questionnaires to measure satisfaction levels with human resource development. The study revealed that the Management Department has implemented training and skills development, seminars and workshops, and curriculum development to enhance the performance of lecturers. Appropriate education and training can improve the skills and knowledge of lecturers, and their involvement in research and community service activities can enhance their ability to produce quality research and contribute to society. Institutional support and project-based or collaborative learning activities can also improve the performance of lecturers and increase student participation and skills. Recognizing and appreciating good lecturer performance can motivate them to continue performing well and contributing to the university and society. In conclusion, optimizing education and training, involvement in research and community service, institutional support, project-based or collaborative learning activities, and recognition and appreciation of good performance is crucial for human resource development to improve the performance of Management Department lecturers at Pattimura University Ambon.